Structural validation of a thermoplastic composite wind turbine blade with comparison to a thermoset composite blade. (February 2021) - Murray, Robynne E.; Beach, Ryan; Barnes, David; Snowberg, David; Berry, Derek; Rooney, Samantha; Jenks, Mike; Gage, Bill; Boro, Troy; Wallen, Sara; Hughes, Scott
Abstract: Reactive infusible thermoplastics have the potential to be advantageous for wind turbine blade composites because they are recyclable at end of life, can have reduced manufacturing costs, enable thermal joining and have similar, and in some cases better, structural properties than traditional thermoset epoxy composites. However, these materials are new to the wind industry and there is risk to investing in a material that has not been validated at a blade scale. Industry cannot adopt a new material such as this without large-scale validation and demonstration of system-level advantages in cost and/or performance. This paper presents structural characterization of a 13-m thermoplastic composite wind turbine blade compared to an identical geometry thermoset epoxy blade. The results of this comparison showed that the flatwise structural static performance and the fatigue performance of the two blades were similar, but the thermoplastic composite blade had increased damping compared to the epoxy blade, which may result in reduced operational loads. Highlights: Structural testing of thermoplastic wind turbine blade compared to thermoset blade. Thermoplastic and thermoset blades as close to identical as possible. Flatwise static and fatigue performance were similar between blades. Thermoplastic composite blade had 5–7 times more damping than the epoxy blade.